2023
DOI: 10.1371/journal.pone.0283351
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and cryptic population structure in a high gene-flow transatlantic fish

Abstract: Lumpfish (Cyclopterus lumpus) is a transatlantic marine fish displaying large population sizes and a high potential for dispersal and gene-flow. These features are expected to result in weak population structure. Here, we investigated population genetic structure of lumpfish throughout its natural distribution in the North Atlantic using two approaches: I) 4,393 genome wide SNPs and 95 individuals from 10 locations, and II) 139 discriminatory SNPs and 1,669 individuals from 40 locations. Both approaches identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 117 publications
4
11
0
Order By: Relevance
“…Although, a divergent subpopulation in mid-Norway was found to be highly differentiated from other Norwegian sampling populations [31]. Moreover, a subset panel of 139 'diagnostic' SNPs revealed that there were at least two genetic clusters in Norway, although not entirely concordant with geography [33]. Further, evidence for the adaptation to local oceanographic features across the pan-Atlantic was also evident in lumpfish [33].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Although, a divergent subpopulation in mid-Norway was found to be highly differentiated from other Norwegian sampling populations [31]. Moreover, a subset panel of 139 'diagnostic' SNPs revealed that there were at least two genetic clusters in Norway, although not entirely concordant with geography [33]. Further, evidence for the adaptation to local oceanographic features across the pan-Atlantic was also evident in lumpfish [33].…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, a subset panel of 139 'diagnostic' SNPs revealed that there were at least two genetic clusters in Norway, although not entirely concordant with geography [33]. Further, evidence for the adaptation to local oceanographic features across the pan-Atlantic was also evident in lumpfish [33]. Indeed, the abiotic environment acts as a selective force on natural populations, shaping and maintaining variation in heritable traits (morphology, physiology, and behaviour) that provide significantly greater fitness in their local environment (i.e., local adaptation) when compared to populations from other environments [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new study on Common lump sh genetic structures revealed natal homing behaviors (Jansson et al 2023). Therefore, ne scale management strategies must account for localized populations found in Mawipoqtapei, an area this study has not sampled.…”
Section: Recommendations For Managementmentioning
confidence: 95%